Powder used for additional production method and ceramic article production method using the same
Patent Information
- Application Number
- JP2022061812
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-12
- Filing Date
- 2022-04-01
- Publication Date
- 2025-04-10
AI Technical Summary
Existing additive manufacturing methods using powders with low light absorption, such as aluminum oxide and gallium oxide, face challenges in achieving high molding precision due to laser light diffusion, leading to difficulties in locally melting the powders and obtaining precise ceramic articles.
A powder composition containing SiO particles and at least one type of oxide particles, such as Al2O3 and SiO2, with specific mass fractions, is used to enhance light absorption and localized heating, ensuring high molding accuracy by efficiently absorbing laser energy and minimizing light scattering.
The powder enables the production of ceramic articles with high accuracy and reduced costs by effectively absorbing laser energy, maintaining precise temperature differences, and preventing deformation, thus improving the overall molding process.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to powders for use in producing ceramic articles by laser-based additive manufacturing techniques. [Background technology]
[0002] With the development of additive manufacturing technology, there is a demand for the realization of a wide variety of dense ceramic articles using additive manufacturing technology. In recent years, raw material powders have been developed for the production of ceramic articles with excellent thermal properties, such as thermal shock resistance and low thermal expansion coefficient, using powder bed fusion, which has excellent manufacturing precision.
[0003] However, when powders with low light absorption, such as aluminum oxide or gallium oxide, are used as raw materials for powder bed fusion, the laser light diffuses within the powder, making it impossible to melt the powder locally, making it difficult to achieve high molding precision.
[0004] In Patent Document 1, by adding a rare earth oxide, which has a higher absorption capacity than Al2O3 for light of the wavelength contained in the laser light, to Al2O3 powder as an absorber, the diffusion of light is suppressed and excellent molding accuracy is achieved. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2019-19051 Summary of the Invention [Problem to be solved by the invention]
[0006] However, because Patent Document 1 uses rare earth oxides as the absorber, the raw material powder is expensive. In order to apply additive manufacturing technology to various applications, inexpensive powder that can be shaped with high precision is required. [Means for solving the problem]
[0007] One aspect of the present invention is a powder used in an additive manufacturing method for performing shaping by irradiating laser light, which contains SiO particles and at least one type of oxide particle other than SiO. The powder excluding the SiO particles contains silicon and aluminum as elements. As the oxide particles other than SiO, at least one type is selected from the group consisting of Al2O3 particles, SiO2 particles, and compound particles of Al2O3 and SiO2. When the components of the powder excluding the SiO particles are converted to oxides represented by Al2O3 and SiO2, x, y, and z representing the mass fractions of Al2O3, SiO2, and SiO in the entire powder satisfy 20 ≦ x < 99.8, 0 < y ≦ 80, and 0.2 ≦ z ≦ 50.
Effects of the Invention
[0008] By using the powder of the present invention, it becomes possible to manufacture and provide ceramic articles at low cost with high shaping accuracy using additive manufacturing technology.
Brief Description of the Drawings
[0009] [Figure 1] It is a diagram conceptually showing the temperature rise characteristics when laser light is irradiated on a powder containing SiO particles and a powder not containing them. [Figure 2] It is a conceptual diagram of a three-dimensional shaping apparatus using the powder bed fusion method. [Figure 3] It is a conceptual diagram explaining shaping using the cladding method.
Modes for Carrying Out the Invention
[0010] An embodiment for carrying out the present invention (hereinafter referred to as "the present embodiment") will be described with reference to the drawings, but the present invention is not limited to the following specific examples at all.
[0011] (Powder) The powder according to the present invention is suitable as a raw material powder for manufacturing ceramic articles containing a compound of Al2O3 and SiO2, which have excellent heat resistance, by additive manufacturing. The powder contains silicon monoxide (SiO) particles and at least one type of oxide particles other than SiO. The oxide particles other than SiO are at least one type selected from the group consisting of Al2O3 particles, SiO2 particles, and compound particles of Al2O3 and SiO2, so that the powder excluding SiO particles contains silicon and aluminum as elements. When the components of all oxide particles other than SiO (powder excluding SiO particles) are converted into oxides represented by Al2O3 and SiO2, x, y, and z, which represent the mass fractions of Al2O3, SiO2, and SiO in the entire raw material powder, satisfy the following relationship: 20≦x<99.8, 0 <y≦80、 0.2≦z≦50
[0012] The SiO particles, Al2O3 particles, SiO2 particles, and Al2O3 and SiO2 compound particles may contain 1000 ppm or less of impurities in addition to the compounds listed above.
[0013] In the present invention, particles contained in a powder refer to so-called primary particles, and they may be in the form of primary particles themselves or secondary particles formed by sintering multiple primary particles. The crystallinity of the particles may be amorphous or crystalline. In the embodiments, the phrase "containing multiple compounds" refers to a powder containing multiple compounds, including a mixture of multiple primary particles made of a single compound, a mixture of one or multiple secondary particles made of multiple primary particles, and a mixture of these. Hereinafter, the primary particles constituting the powder will be simply referred to as particles. For example, if a powder contains independent Al2O3 particles and SiO2 particles, each will be referred to as a particle. If a powder is composed of secondary particles formed by sintering SiO particles, Al2O3 particles, and SiO2 particles, the SiO particles, Al2O3 particles, and SiO2 particles constituting the secondary particles will be referred to as particles, respectively.
[0014] As an example of powder consisting of individual particles, Al2O3 particles are 、 SiO2 particle B、 If the Al2O3 and SiO2 compound particles are designated as C and the SiO particles as D, several combinations are possible. Specifically, the following combinations can be selected: A+D, A+B+D, A+C+D, A+B+C+D, B+C+D, and C+D.
[0015] Below, we will mainly explain the state of the powder when it is unused, but this does not exclude the possibility that particles other than those mentioned above may be contained in the powder when it is used in additive manufacturing. For example, even if the powder is a mixture of Al2O3 particles, SiO2 particles, and SiO particles when it is unused, it may contain composite oxide particles of Al2O3 and SiO2, in which the Al2O3 particles and SiO2 particles have melted and become one after going through the manufacturing process.
[0016] An example of a powder containing multiple primary particles is primary particle A of Al2O3. 、 SiO2 primary particles B 、 When primary particles C are a composite oxide containing aluminum and silicon, and primary particles D are SiO, several combinations are possible. The combinations of primary particles that make up the particles can be selected from A+B, A+C, A+D, A+B+C, A+B+D, A+C+D, A+B+C+D, B+C, B+C+D, C, and C+D.
[0017] In the present invention, the notation of compounds such as Al2O3, SiO2, and SiO does not limit the composition to the stoichiometric ratio shown, and an error of ±30% in the ratio of constituent elements from the stoichiometric ratio normalized by the metal element is allowed. For example, a compound with a ratio of constituent elements of Si:O=1:1.30 is also included in the notation of SiO. In other words, SiO is SiO m It can be expressed as (0.7≦m≦1.3).
[0018] SiO is brown or black in color, and has a relatively higher light absorption capacity for the wavelength of light (laser light) irradiated during fabrication than the Al2O3 and SiO2 contained in the powder. When SiO absorbs laser light, Si changes from divalent to tetravalent, changing the metastable state of SiO to the more stable state of SiO2, reducing its light absorption capacity for laser light. By fabricating SiO, which has these properties, using powder in which aluminum oxide (Al2O3) and silicon dioxide (SiO2) are added as an absorber, the following effects can be achieved.
[0019] The first effect is that the SiO absorber efficiently absorbs the laser light used during manufacturing and becomes hot, which transfers the heat to other compounds present in the area equivalent to the size of the laser light's focus, causing a temperature rise. As a result, the area equivalent to the size of the laser light's focus can be effectively heated locally, clarifying the interface between the area where you want the powder to solidify (the area irradiated with laser light) and the area where you do not want it to solidify (the area not irradiated with laser light), and improving the molding accuracy.
[0020] The second effect is that SiO2 is converted to SiO2, which has low light absorption capacity, by laser irradiation, thereby suppressing light absorption in the solidified portion (solidified portion) where the powder is irradiated with laser light. If the light absorption capacity of SiO2 is reduced to 5 / 6 or less of its pre-laser absorption capacity, irradiating the solidified portion with laser light under the same conditions as during solidification will not be significantly affected by the deterioration of modeling accuracy. In other words, since there is almost no absorber in the solidified portion, there is no temperature rise like before laser irradiation. Therefore, even if the powder adjacent to the solidified portion is irradiated with laser light, deformation or deterioration of the solidified portion is suppressed. As a result, the process margin, such as the laser irradiation conditions, is expanded, and the impact of fluctuations in the irradiation conditions on modeling accuracy can be reduced. To achieve sufficient modeling accuracy, it is preferable that the light absorption capacity of SiO2 alone before laser irradiation is at least 1.2 times higher than the light absorption capacity of the absorber whose composition changes after laser irradiation, and a difference of at least 2 times is preferable.
[0021] The third effect is that after irradiation with laser light, SiO is transformed into SiO2 and incorporated into the molded object, but because SiO2 is composed of elements that make up compounds of Al2O3 and SiO2, such as mullite, the physical properties of the molded object (item) are not impaired.
[0022] In this way, by selectively irradiating the powder according to the present invention with a laser beam to perform shaping, the first to third effects described above can be obtained, and ceramic articles containing compounds of Al2O3 and SiO2, such as mullite, can be shaped with high precision. Furthermore, SiO2 is commercially available as a negative electrode for lithium-ion secondary batteries, and is therefore relatively inexpensive among compounds that can be considered as absorbers.
[0023] These effects will be explained in more detail with reference to the conceptual diagram shown in Figure 1. In Figure 1, the horizontal axis represents the laser light irradiation time, and the vertical axis represents the temperature of the area irradiated with the laser light. Line A represents the temperature rise of a powder containing Al2O3 particles and SiO2 particles but no SiO particles, while line B represents the temperature rise characteristics of a powder of this embodiment containing Al2O3 particles, SiO2 particles, and SiO particles. The powder contains Al2O3 and SiO2 in equal mass fractions. Figure 1 is merely a diagram for explaining the concept, and the temperature rise process is not limited to the linearity shown in the figure.
[0024] Powders that do not contain SiO particles have low light absorption, so the irradiated laser light scatters and localized heating is not possible. This results in poor heating efficiency, and a high input energy per unit volume is required to heat the powder in the irradiated area to the temperature required for sintering or melting and solidifying, resulting in the heating characteristics shown by line A. When a high input energy laser is used to solidify the powder, the scattered laser light raises the temperature of the surrounding powder, making the temperature difference between the laser-irradiated area and the surrounding powder unclear. This results in the formation of a low-density sintered area around the area to be solidified, making it difficult to achieve high molding precision.
[0025] In the present invention, the expression "sintering, or melting and solidifying" does not simply mean that sintering occurs when no powder is melted, or that fusion occurs when no unmelted powder remains. It includes a sintered state in which the powder is bonded to itself, a state in which some unsintered portions are present, liquid phase sintering in which molten material surrounds the powder, and a molten state in which some unmelted powder remains. Hereinafter, "sintering, or melting and solidifying" will be collectively referred to as "solidification."
[0026] When a powder containing SiO particles is irradiated with laser light, the SiO absorbs the laser light and rapidly heats up as shown by line B in Figure 1, resulting in efficient heating and localized heating. This ensures a sufficient temperature difference between the laser-irradiated area and the surrounding area, narrowing the area of the sintered area near the solidified area and achieving excellent molding accuracy. In the solidified area, SiO converts to SiO2, reducing its light absorption ability, resulting in properties similar to those of powders containing no absorber. Therefore, even if a laser beam is irradiated onto an area that has already been molded due to fluctuations in process conditions, the temperature rise is relatively small and the powder is hardly affected. Furthermore, because the area irradiated with laser light and the already solidified area are fused by thermal conduction between the two areas, there are no problems with the connection or boundary strength between the first and second solidified areas. Thus, additive manufacturing using the powder of the present invention, which has the characteristics shown by line B, can achieve the three aforementioned effects.
[0027] When forming a powder bed layer using a recoater in powder bed fusion or spraying powder from a nozzle in cladding, it is important that the powder has a suitable fluidity. Therefore, the powder according to this embodiment preferably has a fluidity index of 40 [sec / 50 g] or less. To ensure such fluidity, each particle is preferably spherical. However, the particle shape is not limited to a spherical shape as long as the above fluidity index is satisfied.
[0028] It is particularly preferable that the SiO particles functioning as absorbers are contained independently of other components, regardless of the state in which other compounds are contained in the powder. This allows for higher light absorption than when multiple SiO particles or secondary particles are formed with other particles. Furthermore, the laser light can more easily reach the absorber, allowing for efficient use of the absorber's light absorption ability. In addition, if the SiO particles are particles independent of other components, the particle size of the SiO particles and the particle size of the other particles can be adjusted separately, making it easier to control the fluidity of the powder and the amount of absorber present within the spot diameter of the irradiated laser light. This point will be explained in detail later.
[0029] When the powder does not contain secondary particles, the average particle size of oxide particles other than SiO is preferably 5 μm or more and larger than that of SiO particles, from the viewpoint of realizing favorable fluidity. More preferably, the particle size is 5 μm or more and at least five times that of SiO particles. Even more preferably, the particle size is 10 μm or more and at least five times that of SiO particles. Furthermore, from the viewpoint of realizing high molding accuracy and making the powder easy to sinter or melt, the average particle size of the particles is preferably 200 μm or less, and more preferably 150 μm or less.
[0030] The average particle size of the SiO particles is preferably 10 μm or less and 1 / 5 or less of the particle size of oxide particles other than SiO. When the SiO particles satisfy this condition, the probability that multiple SiO particles are dispersed near oxide particles other than SiO increases. As a result, the heat generated by SiO absorbing the laser light is efficiently transferred to the oxide particles other than SiO, making it easier to melt the powder in the laser light irradiated area. Considering the dispersibility of SiO in the powder and achieving high packing density, it is preferable that the average particle size of the SiO particles be as small as possible. On the other hand, if the average particle size of the SiO particles is 1 μm or more, scattering into the atmosphere due to laser light irradiation is suppressed, and the amount required as an absorber can be maintained in the powder. Therefore, the average particle size of the SiO particles is preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more but less than 5 μm.
[0031] When the powder contains secondary particles, the average particle size of the secondary particles is preferably 5 μm or more from the viewpoint of realizing fluidity suitable for additive manufacturing. A more preferable average particle size is 5 μm or more and 5 times or more the average diameter of SiO particles. An even more preferable average particle size is 10 μm or more and 5 times or more the average diameter of SiO particles. From the viewpoint of realizing high molding accuracy and ease of sintering or melting the powder, the average particle size of the particles is preferably 200 μm or less, more preferably 150 μm or less. Note that the average particle size of the primary particles that make up the secondary particles may be smaller than the average particle size of the SiO particles.
[0032] The average particle diameter of the SiO particles contained in the powder is determined by observing the powder with a scanning electron microscope (SEM) or the like, performing composition analysis using an energy dispersive X-ray analyzer (EDS) or the like attached to the SEM to identify the regions consisting of SiO, measuring their area, and calculating the circle-equivalent diameter of that area. Measurements are taken for multiple (100 or more) regions consisting of SiO, and the median value is taken as the average particle diameter. This calculation method can be used to calculate the average particle diameter regardless of the type or state of particles. The average particle diameter of secondary particles can also be calculated using a similar method. The powder is observed with a scanning electron microscope (SEM) or the like and composition analysis is performed to distinguish between the regions of secondary particles where primary particles are clustered together and the types of primary particles that make up the secondary particles. The circle-equivalent diameter of the areas of multiple (100 or more) secondary particle regions is calculated, and the median value is taken as the average particle diameter.
[0033] In this embodiment, the particle size refers to the circle-equivalent diameter (Heywood diameter) of each particle. The average particle size of particles of a specific composition contained in a powder does not refer to the particle size of each particle, but is the median value of a group of particles having the same composition, and does not mean that the powder does not contain particles of a size other than that indicated as the average particle size.
[0034] The powder of this embodiment preferably does not contain a resin binder, because the resin binder has a significantly lower melting point than the other compounds contained in the powder, and therefore may be explosively burned away by irradiation with laser light, causing voids or defects in the modeling region.
[0035] Furthermore, if the powder contains sublimable carbon atoms, the carbon may combine with oxygen to form a gas and escape, resulting in voids in the volume previously occupied by the carbon atoms. Furthermore, the carbon atoms may sublimate and rapidly gasify upon irradiation with laser light, potentially adversely affecting the molding process. Specifically, rapid gasification may impart stress to the molten and solidified portions of the powder, resulting in a deformed molded object. Therefore, it is preferable for the powder to contain a small amount of carbon atoms, and it is particularly preferable for the molar ratio of the carbon atoms to be 1000 ppm or less relative to the metal elements of the multiple compounds contained in the powder.
[0036] The powders of this embodiment may be crystalline, amorphous, or a mixture thereof, and the powder and the shaped ceramic article need not be identical in composition, and may differ in particular in oxidation state, nitride state, etc.
[0037] As described above, the powder of the present invention contains SiO particles and one or more types of oxide particles other than SiO. As the oxide particles other than SiO, one or more types of particles are selected from the group consisting of Al2O3 particles, SiO2 particles, and compound particles of Al2O3 and SiO2 so as to contain silicon and aluminum as elements. And, when the components of the oxide particles other than SiO contained in the powder of the present invention are converted into oxides represented by Al2O3 and SiO2, and the mass fractions (mass %) of Al2O3, SiO2, and SiO are represented by x, y, and z, respectively, 20≦x<99.8, 0<y≦80, 0.2≦z≦50 are satisfied. As long as the converted amounts of the aluminum and silicon oxides contained in the powder satisfy the above x and y, it does not matter in what particle form they are contained. As combinations of the compositions of the oxide particles other than SiO constituting the powder, the following combinations are conceivable. SiO2 - Al2O3, SiO2 - Al2O3 - (compound or mixture of Al2O3 and SiO2), SiO2 - (compound or mixture of Al2O3 and SiO2), Al2O3 - (compound or mixture of Al2O3 and SiO2). Considering the stability of the powder composition, SiO2 - Al2O3, SiO2 - Al2O3 - (compound of Al2O3 and SiO2), SiO2 - (compound of Al2O3 and SiO2), Al2O3 - (compound or mixture of Al2O3 and SiO2) are preferable. By using the powder of the present invention, a ceramic article containing a compound of Al2O3 and SiO2 typified by mullite can be manufactured using an additive manufacturing technique. Ceramics containing a compound of Al2O3 and SiO2 are characterized by being superior in thermal shock resistance and high-temperature creep compared to alumina.
[0038] Al2O3 and the compound of Al2O3 and SiO2 have a higher thermal conductivity and a lower viscosity during melting compared to SiO2. Therefore, by using a powder that satisfies x≧20, the heat generated by SiO during laser irradiation can be efficiently transmitted to other particles through Al2O3 or the compound of Al2O3 and SiO2 and melted. And, the melted Al2O3 or the compound of Al2O3 and SiO2 can fuse with the surrounding particles to form a dense shaped object. More preferably, x≧30.
[0039] On the one hand, Al2O3 is suitable for shaping because of its low viscosity during melting, but it has the following problems. When Al2O3 solidifies from the molten state, it tends to grow in a specific crystal axis direction. If crystals randomly start growing at various positions in the molten Al2O3, the gaps between the crystal grains cannot be completely filled, and looseness is likely to occur in the solidified part. Therefore, the powder of the present invention has a mass fraction of Al2O3 of x < 99.8, more preferably x ≤ 99, and an appropriate amount of SiO2 is added. By adding an appropriate amount of SiO2, a compound of Al2O3 and SiO2 is generated during solidification, resulting in multiple phases. Thus, the crystal composition of the solidified part becomes finer, and the generation of looseness is suppressed.
[0040] From the perspective of adding SiO2 to the powder to suppress the occurrence of looseness in the solidified part, the mass fraction of SiO2 is 0 < y, more preferably 1.0 ≤ y, and even more preferably 3.0 ≤ y. On the other hand, SiO2 has a high viscosity during melting. Therefore, if the powder contains too much SiO2, it easily becomes spherical in the molten state and solidifies as it is, and the formed shaped object tends to be porous. In order to form a dense ceramic article, it is preferable to satisfy y ≤ 80, more preferably y < 50. Therefore, in order to form a ceramic article with less looseness and high density, it is preferable that the mass fraction of SiO2 is 1.0 ≤ y < 50, and more preferably 3.0 ≤ y < 50. Also, when the mass fractions x, y, and z of Al2O3, SiO2, and SiO respectively satisfy y < x + z, it is also preferable because a dense shaped object is easily obtained.
[0041] Even when other compositions besides Al2O3, SiO2, and SiO are included, in order to obtain a ceramic article having high thermal shock resistance and a low coefficient of thermal expansion, it is preferable to use a powder with 90 ≤ x + y + z. More preferably, 95 ≤ x + y + z.
[0042] The mass fraction of SiO contained in the powder satisfies 0.2≦z≦50. If the mass fraction z of SiO is less than 0.2, the amount of heat generated per unit time when the powder is irradiated with a laser is insufficient, making it difficult to melt the powder. If the input heat amount is increased by increasing the laser output or extending the irradiation time in order to melt the powder, the heat will be transferred to the periphery of the laser irradiated area, making local melting difficult and reducing the molding accuracy. To efficiently melt the powder locally, it is necessary to satisfy 0.2≦z, and it is more preferable to satisfy 0.5≦z. This condition holds true regardless of whether the SiO particles are independent particles from oxide particles other than SiO or whether the SiO particles form secondary particles with oxide particles other than SiO.
[0043] If the mass fraction z of SiO contained in the powder is 0.2 or more, SiO acts as an absorber.
[0044] If the powder contains more than 50% by mass of SiO, the molding accuracy tends to decrease. This is thought to be because the temperature rise in the area irradiated with the laser light is too rapid, causing the molten material to scatter to the surrounding area. Therefore, to achieve excellent molding accuracy, the SiO content of the powder is set to z≦50.
[0045] As mentioned above, it is preferable that the SiO particles are particles (single particles) independent of other particles and have a small particle size. However, if the powder contains a large number of small-diameter SiO particles, the flowability of the powder may decrease, and a flowability index suitable for additive manufacturing may not be obtained. When the SiO particles are contained in the powder as particles independent of other particles, the SiO content is preferably z≦20.
[0046] When SiO particles are single particles, it is preferable that at least one SiO particle is contained in the region irradiated with the laser beam in order to achieve efficient temperature rise by laser irradiation. Therefore, it is preferable to select the average SiO particle size according to the focal size of the laser beam irradiated on the powder in the manufacturing process. The same applies when SiO particles constitute secondary particles with oxide particles other than SiO.
[0047] From the viewpoint of thermal uniformity during laser irradiation, it is more preferable that two or more SiO particles are stochastically contained within the focal size of the laser light. The distance between SiO particles in the powder is preferably stochastically 100 μm or less, more preferably 50 μm or less. This state is achieved by setting the mass fraction of SiO in the powder to 0.2 or more.
[0048] The state in which two or more SiO particles are contained within the focal size of the laser light can also be achieved by adjusting the focal size of the laser light. Considering that, from the viewpoint of modeling accuracy, the focal size of the laser light is preferably 100 μm or less, the average particle diameter of the SiO particles is preferably 1 μm or more and 10 μm or less. The focal size of the irradiated laser light can be determined according to the desired modeling accuracy, and may be 100 μm or more depending on the required modeling accuracy. In this case, the focal size may be larger than 10 μm as long as two or more SiO particles are contained within the focal size of the laser light. The same can be considered when SiO particles form secondary particles with other particles.
[0049] From the viewpoint of obtaining sufficient light absorption capacity, the light absorption capacity of SiO alone is preferably 10% or more, more preferably 40% or more, and even more preferably 60% or more.
[0050] Because the light absorption capacity of SiO varies depending on the element ratio of Si and O, the preferred ratio of constituent elements is one that deviates from the stoichiometric ratio by no more than ±20%. A silicon to oxygen ratio of approximately 1:1 is particularly preferred, as it exhibits high absorption capacity for light with a versatile wavelength of approximately 1 μm (Nd:YAG). From the perspective of obtaining high light absorption capacity while maintaining the silicon to oxygen composition ratio of SiO, it is more preferable for the SiO particles in the powder to be single particles.
[0051] The ratio of constituent elements of the compounds contained in the powder of this embodiment can be determined using scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscope-energy dispersive X-ray spectroscopy (TEM-EDX), electron beam diffraction, X-ray diffraction, etc. Alternatively, it can also be determined by combining inductively coupled plasma atomic emission spectroscopy (ICP-AES), inductively coupled plasma mass spectroscopy (ICP-MS), X-ray fluorescence analysis, inert gas fusion method, etc.
[0052] A standard spectrometer can be used to measure light absorption. The powder to be measured is placed in a sample dish and irradiated with light of the expected wavelength (the laser wavelength used in the manufacturing process and / or a wavelength close to it), and the reflection is measured using an integrating sphere. The reflection without a sample is used as reference data, and the light absorption can be calculated from the ratio.
[0053] The compositionally altered absorbent becomes a compound that constitutes at least a portion of the ceramic article.
[0054] Here, the assumed wavelength refers to the wavelength of the laser irradiated in the manufacturing process and / or a wavelength in the vicinity thereof. Note that the powder for which the light absorption capacity is measured may be any compound equivalent to that of the ceramic article, and does not necessarily have to be the powder used in manufacturing the ceramic article.
[0055] Due to this reduction in light absorption, parts that have been sintered or melted and solidified by laser irradiation are less susceptible to subsequent laser irradiation, and the shape of the solidified parts is maintained, making it possible to manufacture precise three-dimensional ceramic articles according to the design.
[0056] Since there is concern that prolonged exposure of humans to crystalline SiO2 powder may cause damage to the respiratory system, it is more preferable that the powder contains amorphous SiO2 as the SiO2.
[0057] (Method for manufacturing ceramic articles) The powder of this embodiment is suitable for additive manufacturing, in which a powder is irradiated with a laser beam in accordance with slice data generated based on three-dimensional data of the ceramic article to be manufactured. Specifically, it is used in manufacturing methods using powder bed fusion and cladding. In this manufacturing process, a ceramic article is manufactured by alternately performing the following steps (i) and (ii) multiple times. Step (i) Placing the powder in the laser light irradiation area Step (ii) A step of irradiating the powder with laser light to solidify the powder.
[0058] When manufacturing using a powder bed fusion method, steps (i) and (ii) are performed by spreading the powder of this embodiment on a substrate to a predetermined thickness and then irradiating the substrate with laser light. When manufacturing using a cladding method, steps (i) and (ii) are performed by spraying the powder of this embodiment onto a predetermined location and then irradiating the predetermined location with laser light.
[0059] There are no restrictions on the wavelength of the laser light used for shaping, but it is preferable to use a lens or fiber adjusted to the desired focal size, such as a diameter of 10 μm to 2 mm. The focal size is one of the parameters that affects shaping accuracy, and to achieve a shaping accuracy of 100 μm (0.1 mm), it is preferable that the line width is approximately the same, and that the focal size be 100 μm or less in diameter, depending on the situation. The laser light can be irradiated either continuously or in pulsed form. As the laser light, a laser with a wavelength of approximately 1000 nm, such as an Nd:YAG laser or Yb fiber laser, can be suitably used. This is because the SiO component exhibits particularly high absorption of light with a wavelength of approximately 1 μm.
[0060] Figure 2 is a conceptual diagram of a three-dimensional (3D) printing system using powder bed fusion. As shown in Figure 2, the three-dimensional (3D) printing system includes a powder container 11, a printing unit 13, a recoater unit 15, a laser light source 16, and a scanner unit 17 for scanning the laser light generated by the laser light source 16. The following steps are performed to manufacture a ceramic article. First, the bottom 12 of the powder container 11 is raised to push up the powder 22, and the stage 14 on which the substrate 19 of the printing unit 13 is set is lowered a predetermined distance. Next, the coater unit 15 supplies the powder 22 to the printing unit 12, and the powder 20 is spread to a predetermined thickness over an area larger than the intended ceramic article. According to slice data generated from the three-dimensional data of the ceramic article, the laser light 18 generated by the laser light source 16 is scanned by the scanner unit 14, directly drawing on the powder 20 spread on the substrate 19. The drawn areas are sintered or melted and solidified to solidify, and by repeating this process, a ceramic article 21 is obtained in which solidified areas are stacked one on top of the other.
[0061] The cladding method will be explained using Figure 3. The cladding method is a technique in which powder is ejected from multiple powder supply holes 222 in a cladding nozzle 221, and a laser beam 223 is irradiated onto the area where the powder is focused, thereby successively forming ceramic articles in desired locations. A distinctive feature of this method is that it can be used to form ceramic articles on curved surfaces, etc.
[0062] The atmosphere may also be controlled during the manufacturing process. In addition to air, it is also preferable to use an inert atmosphere containing nitrogen or other rare gases, a hydrogen-containing atmosphere, or a reduced-pressure atmosphere, which favors the reduction of compounds contained in the powder, or an oxygen atmosphere. By controlling the atmosphere in this way, it becomes possible to use powder containing compounds that are oxidized or reduced from the stoichiometric ratio in the manufacturing of ceramic articles.
[0063] In the manufacturing process of this embodiment as described above, by using the powder according to this embodiment, it is possible to obtain a ceramic article that can be shaped stably and with assured shaping accuracy.
[0064] The ceramic article manufactured from the powder according to this embodiment is not limited to an inorganic material in a crystalline state. As long as the desired physical properties are obtained, a portion or a majority of the powder may be in an amorphous state. Furthermore, the above manufacturing process may also produce a ceramic article containing a region in a metallic state or the like, where the powder is reduced.
[0065] (Evaluation method) The porosity of ceramic articles was evaluated using a method based on JIS standard R1634, which is a method for measuring the sintered density and open porosity of fine ceramics. Specifically, for three ceramic articles similar to the samples used to measure mechanical strength, where W1 is the dry mass of the ceramic article, W2 is the mass in water, and W3 is the mass saturated with water, the porosity was calculated using {(W3-W1) / (W3-W2)} x 100 and averaged.
[0066] The composition of the powder or the shaped object was measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES). [Example]
[0067] Specific examples of the powder according to this embodiment are shown below.
[0068] Powders 1 to 21 containing silicon monoxide (SiO) and, in addition to silicon monoxide, aluminum oxide (Al2O3) and silicon dioxide (SiO2) were used to manufacture ceramic articles by powder bed fusion, and their porosity was measured.
[0069] Powders 1 to 15 and 18 to 22 were prepared by mixing the following powders weighed in the amounts shown in Table 1 for 2 hours in a rocking mixer. Powder consisting of Al2O3 particles (Showa Denko Co., Ltd. CB-A20S): average particle size 20 μm Powder consisting of amorphous SiO2 particles (Nippon Steel Chemical & Material Co., Ltd. HS-304): average particle size 28 μm Crushed powder consisting of SiO particles (Japan NER Co., Ltd. SiO-P-002): average particle size 4 μm
[0070] The Al2O3 particles and SiO2 particles are approximately spherical.
[0071] Powders 16 and 17 were produced by the following procedure. The powders listed below were weighed and mixed to obtain the composition ratio shown in Table 2, and then dispersed in water to produce a slurry. Granulated powder with an average particle size of 30 μm was produced from the produced slurry using a spray dryer method, and then heat-treated at temperatures between 600°C and 800°C to produce a granulated powder consisting of spherical secondary particles in which Al2O3 particles and SiO2 particles were contained within each particle. Powder consisting of Al2O3 particles (Taimei Chemical Industry Taimicron TM-DA), average particle size 0.17 μm Powder consisting of SiO2 particles (Nippon Shokubai Seahoster W10), average particle size 0.2 μm
[0072] The powder made of the above-mentioned SiO particles was added to the obtained granulated powder so as to obtain the composition ratio shown in Table 2, and the mixture was stirred for 10 minutes with a rocking mixer.
[0073] Composition analysis of the prepared powders 1 to 22 revealed that all components other than Al2O3, SiO2, and SiO were less than 1 wt%.
[0074] Next, ceramic articles were manufactured using the powders prepared, and the molding accuracy and density of the ceramic articles were evaluated. The ceramic articles were manufactured using a DMP200 from the ProX series (product name) of 3D Systems, equipped with a Yb fiber laser.
[0075] Through the process described above, a rectangular parallelepiped ceramic article measuring 40 mm in length, 6 mm in width, and 5 mm in height was fabricated. An Al2O3 plate was used as the substrate, and the thickness of each powder layer (the value at which the fabrication stage 12 was lowered) was set to 20 μm. A laser beam with a focal spot size of 100 μm and a power of 270 W was irradiated onto the powder at a scanning speed of 500 mm / sec.
[0076] A 40 mm long, 6 mm wide area was drawn at a 100 μm pitch and layered until it reached a height of 5 mm. Since each layer was approximately 20 μm thick, the powder contained particles greater than the thickness of one layer, but these were removed during the initial layering process. Furthermore, the powder layer melted and shrunk in the thickness direction upon irradiation with the laser beam, so the apparent thickness of the powder layer gradually increased with repeated layering, eventually converging to a range of 67–133 μm. Therefore, even if the average particle size of the powder used was larger than 20 μm, this did not pose a problem for use.
[0077] The surfaces of the printed objects were observed using an optical microscope. The surface Ra of the ceramic articles produced using powders 1 to 15 was less than 30 μm, confirming that they were produced with high precision. In particular, the ceramic articles produced using powders 1 to 7, 12 to 14, 16, and 17, which contain SiO2 at 20 wt% or less, had a surface Ra of 25 μm or less, confirming that they were produced with excellent precision. In contrast, the comparative ceramic article produced using powder 22 had an Ra of 40 μm or more, indicating poor manufacturing precision. This is thought to be because powder 22 does not contain SiO2 particles, and the laser light diffuses within the powder during irradiation, causing a wide area of the powder to melt or sinter.
[0078] The evaluation results of density are shown in Tables 1 and 2. Regarding the density of ceramic articles, the porosity was measured and classified into four levels: A if the porosity was 11% or less, B if the porosity was greater than 11% and less than 14%, C if the porosity was greater than 14% and less than 16%, and D if the porosity was greater than 16%.
[0079] In the above classification, A is an extremely good dense body, B is a good dense body, C is a dense body, and D is a porous body or a molded object with many cracks.
[0080] [Table 1]
[0081]
Table 2
[0082] The shaped objects fabricated using Powders 1 to 17 were dense bodies with a density ranging from A to C. In particular, the shaped objects fabricated using Powders 1 to 8, Powders 10 to 13, Powder 16, and Powder 17 that satisfy z ≤ 20 and y < x + z had a density of A or B and an extremely good or good density. In contrast, the comparative shaped objects fabricated using Powders 18 to 20 where x < 20 were porous bodies with a density of D.
[0083] In Comparative Examples 1 to 3, when the spherical melt melted by laser irradiation solidified, many voids remained, resulting in porous ceramic articles. This is thought to be due to the viscosity of SiO2 being higher than that of Al2O3 when it melts. In Comparative Example 4, it is considered that when Al2O3 melts and solidifies, highly anisotropic crystal grains are formed, increasing the gaps and thus resulting in a large porosity.
[0084] The comparative shaped object fabricated from Powder 21 that does not contain SiO2 had a plurality of huge cracks with a width of 10 μm or more, and had a low density of D. This is thought to be because the stress relaxation effect of SiO2 when highly anisotropic Al2O3 melts and solidifies could not be obtained.
[0085] Regarding the comparative examples with many cracks and a D evaluation of density, when heat treatment was performed at about 1700 °C, a crack repair effect was observed.
[0086] The above describes a method for fabricating a shape by melting other metal oxide particles, such as Al2O3 particles or SiO2 particles, using the heat generated by absorbing laser light from SiO particles, which act as an absorber, and then solidifying them. However, the powder of the present invention is not limited to this method. The powder of the present invention can also be used in a method for fabricating a shape by adding a resin adhesive to the powder, melting the resin adhesive using the heat generated by SiO particles absorbing laser light, and then hardening the resin adhesive to bond the particles together with the resin adhesive. The resin adhesive may be added to the powder as particles independent of the other particles, or it may be attached to the surface of Al2O3 particles, SiO2 grains, SiO particles, etc. [Industrial Applicability]
[0087] The powder of the present invention enables the production of high-precision, dense ceramic articles without containing rare earth elements as absorbers, which are used in additive manufacturing processes that use laser light irradiation to create shapes. This makes it possible to provide inexpensive ceramic articles in fields that require complex shapes. [Explanation of symbols]
[0088] 11 powder powder 13 Modeling stage 15 Recoater section 17 Scanner section 16 Laser light source 221 Cladding Nozzle 222 Powder supply hole 223 Laser Light
Claims
1. A powder used in additive manufacturing, which is a method of shaping by irradiating laser light, SiO particles; At least one type of oxide particles other than the SiO particles, The at least one oxide particle is Al 2 O 3 and SiO 2 and In the powder, Al 2 O 3 x represents the mass fraction of SiO 2 A powder characterized in that y representing the mass fraction of and z representing the mass fraction of SiO satisfy the following: 20≦x<99.8 0<y≦80 0.2≦z≦50 90≦x+y+z
2. A powder used in additive manufacturing, which is formed by irradiating a laser beam, SiO particles; Al 2 O 3 particles; and SiO 2 particles, The powder is characterized in that x, which represents a mass fraction of Al 2 O 3 , y, which represents a mass fraction of SiO 2 , and z, which represents a mass fraction of SiO, satisfy the following: 20≦x<99.8 0<y≦80 0.2≦z≦50
3. A powder used in additive manufacturing methods in which a shape is formed by irradiating a laser beam, SiO particles; At least one type of oxide particles other than the SiO particles, the at least one type of oxide particles comprises Al 2 O 3 and SiO 2 ; The powder is characterized in that x, which represents a mass fraction of Al 2 O 3 , y, which represents a mass fraction of SiO 2 , and z, which represents a mass fraction of SiO, satisfy the following: 20≦x<99.8 0<y<50 0.2≦z≦50
4. A powder used in an additive manufacturing method in which a shape is formed by irradiating a laser beam, SiO particles; At least one type of oxide particles other than the SiO particles, the at least one type of oxide particles comprises Al 2 O 3 and SiO 2 ; The powder is characterized in that x, which represents a mass fraction of Al 2 O 3 , y, which represents a mass fraction of SiO 2 , and z, which represents a mass fraction of SiO, satisfy the following: 20≦x<99.8 0<y≦80 0.2≦z≦50 y<x+z 5. The powder of claim 1, 3 or 4, characterized in that the at least one type of oxide particles comprises Al 2 O 3 particles and SiO 2 particles.
6. The powder according to claim 2 or 5, characterized in that the average particle size of the SiO 2 particles is 5 μm or more and 200 μm or less.
7. The powder according to claim 2, 5 or 6, characterized in that the average particle size of the SiO 2 particles is larger than the average particle size of the SiO particles.
8. The powder according to claim 2, 5 or 6, characterized in that the average particle size of the SiO 2 particles is 5 times or more the average particle size of the SiO particles.
9. The powder according to claim 1, 3 or 4, characterized in that the at least one type of oxide particles comprises composite oxide particles of Al 2 O 3 and SiO 2 .
10. The powder according to any one of claims 2 to 9, characterized in that x, y, and z satisfy 90≦x+y+z.
11. The powder according to any one of claims 1 to 9, characterized in that x, y, and z satisfy 95≦x+y+z.
12. The SiO 2 The powder according to any one of claims 1 to 11, characterized in that the mass fraction of y satisfies 1.0≦y<50.
13. The SiO 2 13. Powder according to any one of claims 1 to 12, characterized in that the mass fraction of y satisfies 3.0≦y.
14. The powder according to any one of claims 1 to 13, characterized in that x, y, and z satisfy y < x + z.
15. 15. The powder according to any one of claims 1 to 14, characterized in that the SiO particles are contained as single particles.
16. 9. The powder according to claim 2 or any one of claims 5 to 8, characterized in that the average particle size of the SiO particles is 1 / 5 or less of the average particle size of the Al2O3 particles.
17. The powder according to any one of claims 1 to 16, characterized in that the average particle size of the SiO particles is 1 µm or more and 10 µm or less.
18. The SiO 2 As the amorphous SiO 2 18. Powder according to any one of the preceding claims, characterized in that it comprises
19. 19. The powder according to claim 1, characterized in that the particles constituting the powder include secondary particles of the SiO particles and oxide particles other than the SiO particles.
20. 1. A method for making a ceramic article, comprising the steps of: depositing a powder layer using the powder according to any one of claims 1 to 19; irradiating the powder layer with a laser beam to solidify it; The method for producing a ceramic article is characterized in that the above-mentioned step is carried out multiple times.
21. The method for manufacturing a ceramic article according to claim 20, wherein the laser light is irradiated in accordance with slice data generated from three-dimensional data of the ceramic article.
22. 22. The method for producing a ceramic article according to claim 20 or 21, wherein the laser light is light from an Nd:YAG laser or an Yb fiber laser.